Basil, Ocimum basilicum, yield in northern latitudinal aquaponic growing conditions. Issue 1 (15th June 2021) - Abbey, Marie; Anderson, Neil O.; Yue, Chengyan; Schermann, Michele; Phelps, Nicholas; Venturelli, Paul; Vickers, Zata
Abstract: The need for yield research is increasing with the popularity of aquaponic food production systems where plants and fish are grown together in a recirculating system. Our objective was to compare the yield of three basil cultivars ("Elenora, " "Genovese, " "Nufar, " Ocimum basilicum ) in four configurations (greenhouses: floating raft DWS, ebb & flow, A‐frame; warehouse: floating raft; 1–8 tank replications/treatment) as well as a soilless control to establish a baseline for aquaponic producers in northern latitudes. We also tested whether basil yield varied among fish types: yellow perch, Perca flavescens, goldfish, Carassius auratus, tilapia, Oreochromis spp., and koi, Cyprinus carpio . Fish tank water temperature, nitrite, and alkalinity levels differed significantly over seasons (summer, winter). There was a significant decrease in basil production in all aquaponic systems that used koi (greenhouse, warehouse). No significant difference in basil yield was found among greenhouse and aquaponic systems for perch, tilapia, or goldfish nor among the basil "Elenora, " "Genovese, " and "Nufar." Considerable variation occurred in yield although most of it occurred in fresh weights, being reduced significantly in dry weights. The effects of growing koi fish on reducing aquaponic production of basil is noteworthy, although future research is needed to the exact cause.